Analysis of the Integrated Smart Maintenance System to Support Aircraft Readiness in Air Defense Facing Regional Crises - Novian, Randy; Setiawan, Asep; Hasanudin, Usni; Kurnia, Asep (Indonesian Journal of Multidisciplinary Science, 2026)
This research examines the necessity and implementation of the Integrated Smart Maintenance System (ISMS) as a strategic solution to enhance the aircraft readiness of the Indonesian National Armed Forces (TNI) amidst the growing complexity of regional and global security challenges. The study is grounded in the fact that the current aircraft maintenance system within TNI remains reactive, fragmented, and lacks predictive capabilities supported by artificial intelligence. These limitations result in high aircraft downtime, delayed logistics support, and inefficiencies that directly affect Indonesia’s air defense credibility. The study employs a qualitative approach using a case study method, combining in-depth interviews with TNI logistics officials, aircraft technicians, and defense industry stakeholders (PT Dirgantara Indonesia and GMF AeroAsia), along with comprehensive document analysis and literature review. The theoretical framework encompasses Regional Security Theory (Buzan & Wæver), Air Defense Theory, Maintenance Theory (Tjiptono & Diana), Information System Theory (McLeod), and strategic planning and forecasting concepts. The findings reveal fundamental weaknesses in TNI’s maintenance system, including poor data integration, the absence of predictive algorithms, limited spare parts availability, and weak coordination across services and industry. Nevertheless, SWOT analysis indicates strong opportunities for ISMS development, supported by defense modernization initiatives, national industrial readiness, and the advancement of digital technologies such as AI, IoT, and data analytics. ISMS is projected to increase aircraft readiness to 70–80%, reduce downtime, strengthen deterrence capability, and establish a digital maintenance culture within TNI.